Representations and Writing Practices in the Latin American Context. State of the Art - MORENO PINEDA, VÍCTOR ALFONSO (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This review presents the state of the art of research on representations and writing practices in the Latin American context. Ten researches on social representations of writing and fourteen researches on writing practices, advanced in diverse social and cultural contexts, are collected. The information was gathered from the repositories Redalyc, Dialnet and Scielo and from specialized journals; only research articles that explicitly had the structure introduction, theoretical framework, methodology, results and conclusion were taken into account. To organize the information, an analytical content matrix was designed. This matrix served to extract the relevant info rmation and organize it in the analytical categories defined a priori : objectives, theories, methods and results. This document comprises three sections. First, the methodology used to systematize the information of the articles is explained. Then, the ana lytical categories in which the state of the art was organized are presented. And finally, there is a discussion about the general tendencies of the reviewed works and some reflections on alternatives and research projections are offered in the field of so cial representations and writing practices